An intelligent system for quality measurement of Golden Bleached raisins using two comparative machine learning algorithms - Karimi, Navab; Ranjbarzadeh Kondrood, Ramin; Alizadeh, Tohid (Measurement, 2017)
Abstract In this research, an expert system is provided for measuring and recognizing the quality and purity of mixed (pure-impure) raisins using bulk raisins’ images. For this purpose, by utilizing a machine vision setup 1400 images of the raisins were captured in the several ranges of mixture (from 5 to 50%). Then, totally 146 textural features were obtained using four methods of gray-level histograms, gray level co-occurrence matrix (GLCM), gray level run-length (GLRM) matrix, and local binary pattern (LBP). Principal Components Analysis (PCA) was used in order to find the optimum features from the extracted features. Accordingly, Artificial Neural Network (ANN) and Support Vector Machine (SVM) were used for classifying the mixtures. In comparison to ANN, using top 50 features, SVM classifier had more efficient and accurate classification results (averagely 92.71%). The results of the proposed approach can be used in designing a system for purity and quality measuring of raisins.
Keywords: Image processing; Golden Bleached Raisin (GBR); Bulk textures; Textural features; Support Vector Machine; Artificial Neural Network